A randomized assessment of adding the kinase inhibitor lestaurtinib to first-line chemotherapy for FLT3-mutated AML - Knapper, Steven (Blood, 2017)
The clinical benefit of adding FMS-like tyrosine kinase-3 (FLT3)-directed small molecule therapy to standard first-line treatment of acute myeloid leukemia (AML) has not yet been established. As part of the UK AML15 and AML17 trials, patients with previously untreated AML and confirmed FLT3-activating mutations, mostly younger than 60 years, were randomly assigned either to receive oral lestaurtinib (CEP701) or not after each of 4 cycles of induction and consolidation chemotherapy. Lestaurtinib was commenced 2 days after completing chemotherapy and administered in cycles of up to 28 days. The trials ran consecutively. Primary endpoints were overall survival in AML15 and relapse-free survival in AML17; outcome data were meta-analyzed. Five hundred patients were randomly assigned between lestaurtinib and control: 74% had FLT3-internal tandem duplication mutations, 23% FLT3–tyrosine kinase domain point mutations, and 2% both types. No significant differences were seen in either 5-year overall survival (lestaurtinib 46% vs control 45%; hazard ratio, 0.90; 95% CI 0.70-1.15; P = .3) or 5-year relapse-free survival (40% vs 36%; hazard ratio, 0.88; 95% CI 0.69-1.12; P = .3). Exploratory subgroup analysis suggested survival benefit with lestaurtinib in patients receiving concomitant azole antifungal prophylaxis and gemtuzumab ozogamicin with the first course of chemotherapy. Correlative studies included analysis of in vivo FLT3 inhibition by plasma inhibitory activity assay and indicated improved overall survival and significantly reduced rates of relapse in lestaurtinib-treated patients who achieved sustained greater than 85% FLT3 inhibition. In conclusion, combining lestaurtinib with intensive chemotherapy proved feasible in younger patients with newly diagnosed FLT3-mutated AML, but yielded no overall clinical benefit. The improved clinical outcomes seen in patients achieving sustained FLT3 inhibition encourage continued evaluation of FLT3-directed therapy alongside front-line AML treatment. The UK AML15 and AML17 trials are registered at www.isrctn.com/ISRCTN17161961 and www.isrctn.com/ISRCTN55675535 respectively.